Chronotype, sleep hygiene, and sleep characteristics among athletes of different disciplines - Borghi, S.; Bizzozero, S.; Vitale, J. A.; Tallini, E.; Corazza, F.; La Torre, A.; Banfi, G.; Codella, R. (International Journal of Sports Medicine, 2025)
The objective of the study was to assess chronotype, sleep hygiene, and sleep characteristics of Italian athletes in order to identify differences among sport disciplines (team- vs individual-sports), level of competition (Elite vs Non-Elite) and sexes. Moreover, correlations between chronotype, sleep hygiene and sleep quality were evaluated. Two hundred eighty Italian athletes (Females:113; Males:167) participated in the study. They completed the Pittsburgh Sleep Quality Index (PSQI), the Sleep Hygiene Index (SHI) and the MorningnessEveningness Questionnaire (MEQ). Among the athletes, 66.4% were intermediate-type, 21.8% were morning-type and 11.8% were evening-type. 55.4% of the sample was classified as good sleeper (PSQI<5), while 16.1% had poor sleep hygiene (SHI=35). Females had higher total sleep time (p=0.022) than males. Individual-sports showed more morning-oriented score (p=0.001) and lower PSQI (p=0.006) and SHI (p<0.001) scores, with earlier timing of sleep (bedtime:p<0.001; wake-up time:p<0.001) compared to teamsports. Elite athletes exhibited greater sleep efficiency (p=0.009), and lower sleep latency (p=0.018) and wake after sleep onset (p=0.043) than Non-Elite athletes. Additionally, significant correlations were found between PSQI and SHI (r=0.43, p<0.001), and between MEQ and SHI (r=-0.35, p<0.001). This study yields crucial insights into the sleep behaviors of Italian athletes, revealing that nearly half of the sample were bad sleepers.